Oil price change and economic growth: evidence from Net Sub-Saharan Africa oil exporting countries - Babuga, Umar Tijjani; Mohd Naseem, Niaz Ahmad (Econjournal, 2022)
This paper aimed at examining the long run relationship between the oil price change and economic growth for Sub-Saharan Africa (SSA) net oil exporters (Angola, Cameroon, Congo (Democratic Republic), Congo (The Republic), Equatorial Guinea, Gabon and Nigeria) with the sole purpose of pinpointing the threshold level where an increase beyond that is no longer or even contributing negatively to the economic growth of these countries. Based on the dynamic heterogenous panel PMG estimation, the empirical results show that a threshold level exists between oil price increase and economic growth for these countries, where an increase in oil price (op2) depicts a negative sign which is non-linear and at the same time signifying an inverted u shape relationship with the real GDP (rgdpc) as an indicator of economic growth. As the finding suggested, the rising oil price above certain threshold triggers fall in real GDP. However, the economies of these countries depend largely on oil revenue, therefore, economic diversification, saving and investing the excess of crude oil revenue at the time of higher oil prices became necessary to them in order to prevent their economies against the vagaries of volatility and uncertainty of the oil price.